EKSISTENSI TOKOH UTAMA DALAM NOVEL“HOME WEET LOAN” (KAJIAN PSIKOANALISIS HUMANIS DIALEKTIK) - Emmya Pepayosa Bangun; Rosmaini (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This research is a qualitative descriptive study that dissects a phenomenon with words, not numbers. The data obtained are narratives and excerpts of dialogue or monologues from the novel “Home weet Loan” by Almira Bastari. This study analyzes how the meaning and purpose of Kaluna's life, the main character in the novel “Home weet Loan” is based on the fulfillment of her existential needs as a human being. Through Erich Fromm's dialectical humanist psychoanalytic approach, the fulfillment of human existential needs is found, which are divided into: relatedness, rootedness, transcendency, unity, and identity. Kaluna is ultimately able to achieve freedom and autonomy, and to be active according to what she believes.